SCIENCE IN A DEMOCRATIC SOCIETY. - Kitcher, Philip (Poznan Studies in the Philosophy of the Sciences & the Humanities, 2011)
Claims that science should be more democratic than it is frequently arouse opposition. In this essay, I distinguish my own views about the democratization of science from the more ambitious theses defended by Paul Feyerabend. I argue that it is unlikely that the complexity of some scientific debates will allow for resolution according to the methodological principles of any formal confirmation theory, suggesting instead that major revolutions rest on conflicts of values. Yet these conflicts should not be dismissed as irresoluble.